Sagot :
Answer:
2
Step-by-step explanation:
Try 1 first if this is one of the zeros of the expression (since this is a cubic one)
x³ - 2x² - 5x + 6
1 - 2 - 5 + 6 = 7 - 7 = 0
So, 1 is one of the zeros of the expression, thus (x - 1) is its one factor.
Dividing x³ - 2x² - 5x + 6 by x - 1, we get x² - x - 6 as a result.
Sum of zeros of x² - x - 6 = -b/a = -(-1)/1 = 1
Add 1 (one of the zeros) by 1 (the sum of zeros of x² - x - 6), and we get 2 as the final result.
That's all. Hope you get a perfect score.